Comparisons and Impacts of the Basic Components of Sarcopenia Definition and Their Pairwise Combinations in Gastric Cancer: A Large-Scale Study in a Chinese Population - Zhang, Feng-Min; Zhang, Xian-Zhong; Shi, Han-Ping; Zhang, Zhao; Wang, Su-Lin; Shen, Zi-Le; Chen, Xiao-Lei; Shen, Xian; Yu, Zhen; Zhuang, Cheng-Le (Frontiers in Nutrition, 2021)
Background and aims: Sarcopenia is negatively associated with clinical outcomes. However, sarcopenia definitions are inconsistent across the international consensuses. The purpose of this study is to compare the impacts of basic definition components of sarcopenia and their combinations on postoperative complications and overall survival, aiming to find the best sarcopenia definition to stratify the prognosis in Asian population. Methods: A total of 1307 patients who underwent curative surgery for gastric cancer from July 2014 to May 2019 were prospectively included. Basic sarcopenia components were measured preoperatively, including low skeletal muscle mass index (LSMI), low skeletal muscle radiodensity (LSMD), low handgrip strength (LHGS), and low gait speed (LGS). Among them, LSMI and LSMD were measured using CT post-processing software, LHGS were measured using electronic hand dynamometer, while LGS were represented by 6-meter walk speed. Results: For single basic component, muscle function parameters (LHGS or LGS), but not muscle composition parameters (LSMI or LSMD) showed association with postoperative complication and mortality. For combinations of basic combinations, all statistically significant combinations included at least one muscle function parameter. The combination of muscle composition (LSMI or LSMD) plus muscle function (LHGS or LGS) had significantly higher area under the curve in the prediction of postoperative complication compared to the combinations of two muscle function parameters (LSMI plus LSMD) or two muscle composition parameters (LHGS plus LGS). Conclusions: Compared to muscle composition parameters (LSMI and LSMD), muscle function parameters (LHGS and LGS) are better predictors of postoperative complications and overall survival, which should be considered as the principal determinant in the sarcopenia definition. Sarcopenia definition consists of muscle function (LHGS or LGS) plus muscle composition (LSMI or LSMD) is better than combinations of two muscle function parameters (LHGS plus LGS) or two muscle composition parameters (LSMI plus LSMD).